1974
DOI: 10.1002/pen.760140805
|View full text |Cite
|
Sign up to set email alerts
|

Linear polycarboranesiloxanes

Abstract: Aspects of the present status of structure‐property correlations for linear polycarboranesiloxanes which contain rigid carborane cages and flexible siloxane in‐chain linkages are discussed. Low temperature secondary transitions, glass transitions, crystallization and melting transitions, and high temperature chemical transformations in inert and air atmospheres are emphasized. The linear polymers serve as the basis for new high‐temperature elastomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…25 The char yield at 800°C increased with the increase in CB-PEPA, which was similar to that previously reported. 26 And CB-PEPA had the highest char yield up to 90.6%. It could be ascribed to the formation of excellent thermal stability boron trioxide on sample’s surface, thus providing a layer of protection to prevent further degradation.…”
Section: Resultsmentioning
confidence: 97%
“…25 The char yield at 800°C increased with the increase in CB-PEPA, which was similar to that previously reported. 26 And CB-PEPA had the highest char yield up to 90.6%. It could be ascribed to the formation of excellent thermal stability boron trioxide on sample’s surface, thus providing a layer of protection to prevent further degradation.…”
Section: Resultsmentioning
confidence: 97%
“…(Figs. [3][4][5]. These new polymers have also been characterized by 'H, 13C and 29SiNMR, TR, and elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A number of results were found that may have otherwise gone unnoticed in briefer studies (16). The cyclization mechanism of degradation which occurs for polydimethylsiloxane is not operative for polyearboranesiloxanes.…”
Section: Thermal Analysis Of a Number Of Linear Polycarboranesiloxanementioning
confidence: 99%
“…For chain-end initiation followed by partial unzipping -DN/dt = 0 [15] and from [9], [11] and [15] with integration DP/DP = 1-C ο [16] For initial end-group depolymerization followed by complete unzipping and combining [8], [9], [11] and [17] followed by integration yields…”
Section: Combining [10] [11] and [13] Into [9] With Integration Givementioning
confidence: 99%